Peanut worms of the phylum Sipuncula from the Nha Trang Bay (South China Sea) with a key to species - Adrianov, Andrey V.; Maiorova, Anastassya S. (Zootaxa, 2012)
Sipunculan worms from the Vietnamese waters are still poorly investigated, while they are well known from Chinese andTaiwanese waters of the South China Sea. During the years 2008–2010, therefore, we collected sipunculans from NhaTrang Bay in South Vietnam. Twenty species of peanut worms representing eleven genera and five families of the phylumSipuncula are recognized from more than one thousand individuals collected from various biotopes. Fifteen species arenew records for Nha Trang Bay with Nephasoma pellucidum being a new record for the South China Sea. Species accountsinclude the most important taxonomic characters as well as quantitative characteristics, distributions, and specific biotopedata. All species were illustrated in living conditions with everted introvert and tentacular apparatus. Accordingly, a key up to species level is provided.